2016
DOI: 10.1002/lary.26110
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual analysis of the male-to-female transgender voice after glottoplasty-the telephone test

Abstract: NA Laryngoscope, 127:875-881, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 32 publications
0
17
1
2
Order By: Relevance
“…Real or perceived impairments to voice can significantly diminish people's functionality and quality of life. For transgender individuals in particular, voice and communication have an enhanced degree of importance as a direct reflection of identity and a source of anxiety about being misidentified 19,20 . Although voice has been recognized to be of critical importance to transgender patients, fundamental understanding of transgender voice remains limited to date, and it is unclear how best to assess and follow voice changes in transgender patients during and after treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Real or perceived impairments to voice can significantly diminish people's functionality and quality of life. For transgender individuals in particular, voice and communication have an enhanced degree of importance as a direct reflection of identity and a source of anxiety about being misidentified 19,20 . Although voice has been recognized to be of critical importance to transgender patients, fundamental understanding of transgender voice remains limited to date, and it is unclear how best to assess and follow voice changes in transgender patients during and after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, there are few studies in the literature regarding transgender voice, and many are limited by small sample size, inconsistent methods, and lack of standardized data reporting tools 11,19,20,22–25 . Few report acoustic data, and those studies that do focus largely on time‐based acoustic measures such as jitter, shimmer, NHR, and vowel formants which have generally noted only a weak to moderate correlation 9 .…”
Section: Discussionmentioning
confidence: 99%
“…204 Being perceived as male is negatively correlated to personal satisfaction of the voice, even if the fundamental frequency is within the female range. 205 However, Hancock and colleagues, 206 reported that QOL ratings in TW are strongly correlated with their self-rated perception of voice and only moderately related to how others perceive their voice.…”
Section: Part 4: Other Health Considerations For Twmentioning
confidence: 99%
“…Es ergab sich für 5 Patientinnen (23,8 %) kein stimmbezogenes Handicap. 6 Patientinnen (28,6 %) lagen im Bereich eines geringen Handicaps, ebenfalls 6 Patientinnen (28,6 %) waren der Kategorie "mittelschweres Handicap" zuzuordnen und 4 Patientinnen (19,1 %) wiesen ein hochgradiges stimmliches Handicap auf [49]. Bezogen auf eine Transsexualität wurde in der Vergangenheit die mangelnde Spezifität allgemeiner stimmbezogener Fragebögen kritisiert und hinterfragt, ob mit diesen Messinstrumenten die ganze Stimmproblematik transsexueller Patientinnen erfasst werden kann [50].…”
unclassified
“…Die Indizes von 21 transsexuellen Patientinnen nach erfolgter Glottoplastik wurden mit den altersabhängigen Staninen sowie mit den allgemeinen Durchschnittswerten der weiblichen Normierungsstichprobe verglichen. Besondere Defizite zeigten sich in der Subskala "Freunde, Bekannte und Verwandte" [49]. In der folgenden Arbeit wird ein Addendum zu den beiden Fragebögen VHI und FLZ vorgestellt, mit dem spezifische Aspekte der Stimmtherapie in der Transition von Mann zu Frau erfasst werden.…”
unclassified